Do sleep changes mediate the anti‐depressive and anti‐suicidal response of intravenous ketamine in treatment‐resistant depression?. (16th June 2021) - Rodrigues, Nelson B.; McIntyre, Roger S.; Lipsitz, Orly; Cha, Danielle S.; Cao, Bing; Lee, Yena; Gill, Hartej; Lui, Leanna M. W.; Cubała, Wiesław J.; Ho, Roger; Shekotikhina, Margarita; Teopiz, Kayla M.; et al.
Summary: Sleep disturbances are commonly reported in patients with treatment‐resistant depression (TRD). Available data have shown that intravenous (IV) ketamine is an effective treatment for patients with TRD and growing data suggest ketamine may improve overall sleep architecture. In the present study, we evaluated whether changes in sleep symptoms mediated the anti‐depressive and/or anti‐suicidal effects of IV ketamine and whether improvement in sleep correlated with a higher likelihood of achieving response or remission. Adults with TRD received four infusions of IV ketamine at a community‐based clinic. Total depressive symptom severity was measured with the Quick Inventory Depressive Symptoms Self‐Report 16‐Item (QIDS‐SR16 ) at baseline and was repeated across four infusions. Suicidal ideation (SI) and four sleep symptoms were measured using the SI item and the five sleep items on the QIDS‐SR16 . A total of 323 patients with TRD received IV ketamine. Self‐reported improvements in insomnia, night‐time restlessness, hypersomnia, early morning waking, and total sleep were significant partial mediators to the improvements observed in depression severity. Similarly, insomnia, night‐time restlessness, early morning waking and total sleep improvements mediated the reduction of IV ketamine on SI. All sleep items, except for hypersomnia, were associated with an increased likelihood of achieving response or remission. Notably, each point improvement in total sleep score was significantly associated with achieving responder/remitter status (odds ratio 3.29, 95% confidence interval 2.00–5.41). Insomnia, sleep restlessness, early morning waking and total sleep improvements were significant mediators of antidepressant and anti‐suicidal improvements in patients with TRD receiving IV ketamine.